CONVERSION OF RICE STRAW TO FERMENTABLE SUGARS AND BIOETHANOL BY MFEX PRETREATMENT AND SEQUENTIAL FERMENTATION - Shawky, Bahaa Talaat (MATTER: International Journal of Science and Technology, 2017)
The global rise in energy consumption, predicted increase in energy demands, price fluctuations, depletion and drawbacks of fossil fuels have converged to create an urgent need to develop more sustainable energy systems based on renewable feedstocks. Lignocellulosic materials are attractive feedstocks for bioethanol production. Rice straw is a promising feedstock for sustained production of biofuel. Bioethanol from lignocellulosic biomass could be a promising technology though the process has several challenges such as efficient pretreatment methods for delignification of lignocellulosics. Pretreatment is a prerequisite step for increasing the enzymatic digestibility for conversion to biofuels in biorefineries. The merits of a new and promising pretreatment called Multipurpose Fiber Expansion (MFEX) method for pretreating rice straw for bioethanol production was studied, where rice straw was treated with steam and carbon dioxide in sequence to make use of the synergistic effects obtained under pressure and moderate temperature for a few minutes and then rapidly releasing the pressure. A total reducing sugars of 645mg/g dry treated rice straw was achieved within 24 hours hydrolysis using laboratory prepared cocktail cellulolytic and hemicellulolytic enzymes. Of this total, 400 mg/g was glucose, which was rapidly fermented within 24 hours by a genetically-engineered Klebsiella oxytoca P2 leading to bioethanol yield of 375 mg/g dry treated biomass. Biofuels provide a potential and promising green alternative to avoid the global environmental crises that arise from dependence on fossil fuels. Conversion of glucose as well as xylose to bioethanol needs some improved co-fermentation technologies, to make the whole process cost effective.